ANCIENT SCRIPTURES: HISTORY, LINGUISTICS, AND RESEARCH (Bulletin of Innovative Research, 2026)
this article provides a scholary analysis of the system of written signs of the ancient Maya and the history of the decipherment of their writing. Mayawriting is recognized as one of the most complex hieroglyphic systems in the history of humanity, and it is emphasized that is reading and decipherment required several centuries. Special attention is paid to the research conducted by scholars qho made a significand contribution to the study and decoding of the Maya writing system.